The effect of surface roughness of silicone-based resilient liner materials on the adherence of Candida albicans and inhibition of Candida albicans with different disinfectants - ÖZKAN, YASEMİN (Quintessence Publishing Co., Ltd, 2009)
Purpose: The objective of the present study was to evaluate surface roughness and adherence of Candida albicans and to determine the effectiveness of denture cleansers in the disinfection of silicone-based soft lining materials. Materials and Methods: Two types of silicone-based soft lining materials (four room temperature polymerised soft lining materials [RTPSLM]: Ufi Gel P, Ufi Gel C, Mollosil and Soft-Liner; and two high temperature polymerised soft lining materials [HTPSLM]: Moloplast B and Luci Soft) and seven denture cleansers (Efferdent, Polident, Steradent, Corega, Denclen, Klorhex and Axion) were tested in the present study. For each soft lining material, 56 samples (10 mm · 10 mm · 3 mm) were prepared. Surface roughness measurements were made using a profilometer with an optical scanner probe. All samples were ultrasonically cleaned in water for 15 s, autoclave sterilised and contaminated with C. albicans solutions for adherence assay evaluation. After the evaluation, the samples were immersed in seven different denture cleansers. The results were expressed as the ratio of cells remaining after each cleanser in comparison with the control group. Results: HTPSLM showed a lower surface roughness value (2.21 ± 0.30 lm) than RTPSLM (2.39 ± 0.40 lm), but these differences were not statistically significant (P > 0.05). Also, HTPSLM showed lower adhesion of C. albicans (mean ranks 136.35) than RTPSLM (mean ranks 138.64), but the differences were not statistically significant (P > 0.05, one- or two-way analysis of variance). In the C. albicans removal test, all denture cleansers showed a strong effect on both silicone-based soft lining materials. HTPSLM showed lower removal activity (mean ranks 30.01) than RTPSLM (mean ranks 25.86), but these differences were not statistically significant (P > 0.05). Although there were no significant differences between disinfectants on both silicone-based soft lining materials, Axion was found to be the most effective disinfectant. Corega, Polident, Denclen, Steradent and Efferdent showed the most effective cleansing, respectively. Conclusions: RTPSLM and HTPSLM did not show significant differences in the surface roughness value; also they showed no significant differences in the adhesion rate of C. albicans. All tested silicone-based soft lining materials showed adherence of C. albicans after contamination procedures, and removal activity for C. albicans was observed in all tested silicone-based soft lining materials after disinfection procedures. © Quintessence.
Keywords: C. albicans; Disinfections; Silicone-based soft lining materials; Surface roughness